Collaborative Governance in Plastic Waste Recycling in Medan City: Integrating Informal Sector, Community Participation, and Policy - Sihaloho, Ulfah Oktarida; Rusliadi, Rusliadi (Department of Public Administration, Muhammadiyah University of Makassar, 2025)
Medan City faces low household participation in waste sorting—only 20 % regularly—and limited integration of the informal sector, which nonetheless collects approximately 30 % of recyclable materials. This study examines the role of collaborative governance in enhancing community engagement, formalizing the contributions of waste pickers, and improving policy coordination to establish a sustainable plastic recycling system. A qualitative case study design was adopted, comprising 15 in‑depth interviews with representatives from government agencies, informal sector actors, recycling businesses, and community members; field observations at three TPS/TPA sites; and analysis of relevant policy documents. Results reveal that inadequate sorting facilities and deficient public education impede household involvement; waste pickers operate without formal incentives, leading to suboptimal participation; and overlapping institutional mandates hinder effective policy implementation. In response, an integrated education campaign with the distribution of 10000 sorting bins over six months, direct subsidies of IDR 50000 per ton for registered waste pickers, and the establishment of a quarterly cross‑sectoral coordination forum are proposed. Implementation of these measures is projected to increase sorting rates to 60 % and integrate 80 % of informal actors into the formal recycling framework.